Decreasing Methylene Blue Using Expanded Perlite - Utami, Mardiana Rimba; Riyani, Kapti; Setyaningtyas, Tien (Proceedings of the International Conference on Green Technology, 2026)
The industrial sector and household is a significant contributor to water pollution. Pollutants such as acids, dyes, heavy metals, and other toxic chemicals can have devastating effects on the environment, even at low concentrations. Methylene blue in water can undergo photodegradation with the assistance of sunlight, but this reaction occurs slowly and is not in line with its accumulation rate in the water. This can lead to environmental damage due to the presence of methylene blue, which is difficult to degrade and impairs water quality. To mitigate these risks, adsorption used to wastewater treatment. This study investigates the effectiveness of perlite as an adsorbent for decreasing methylene blue from water, examining the effects of pH, contact time, and initial concentration on adsorption kinetics and isotherms. The optimal pH for methylene blue adsorption is 9, with a contact time of 180 minutes. The maximum adsorption capacity of perlite is 3.87 mg/g, with the adsorption process following pseudo-second-order kinetics and the Langmuir isotherm model, indicating a chemical and homogeneous single-layer adsorption mechanism.